Content validity of scenes of the declarative tactical knowledge test in volleyball - DTKT:Vb - de Conti Teixeira Costa, G.; de Oliveira Castro, H.; de Araujo Cabral, F.; Perez Morales, J. C.; Greco, P. J. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2016)
Declarative Tactical Knowledge Tests are presented as important evaluation tools for the teaching-learning-training process regulation. This study aimed to establish the content validity of scenes of the Declarative Tactical Knowledge Test in Volleyball - DTKT:Vb. Five male coaches of the Brazilian Volleyball team who worked with male athletes participated as judges, being responsible for training formation categories up to 21 years, experts in the sport, with minimum ten years of experience. The judges evaluated 212 scenes containing extremity attack (n=55), central attack (n=33), setting (n=68) and block (n=60) situations and used a 1-5 point likert scale to assign a score to the scene according to requisites image clarity, practical relevance and item representativity. The Content Validity Coefficient (CVC) was used to determine the CVC for each scene and the instrument as a whole, with cutoff point of 0.80. The results demonstrated that "image clarity" (CVC=0.92), "practical relevance" (CVC=0.96) and "item representativity" criteria (CVC=0.96) showed satisfactory levels. After calculating CVC, the ecological validity of scenes was determined, which consists of the selection of scenes where there was convergence among decision made by judges and decision made by athletes. Thus, from 212 scenes initially prepared, 66 have been validated. Scenes validated using CVC enabled the evaluation of the Declarative Tactical Knowledge, assisting in the planning of teaching-learning-training processes of male volleyball athletes.